IMPACT OF EXTRACRANIAL COMPLICATIONS IN PATIENTS WITH SEVERE BRAIN INJURY - Krasnenkova M. B.; Bektemirova N. T. (Galaxy International Interdisciplinary Research Journal, 2023)
Given the high prevalence of traumatic brain injury (TBI) and high mortality, predicting outcomes for these patients and their families is of great importance. Early determination of prognosis after TBI is a priority for relatives and physicians involved in the care of these patients. Not only damage to the medulla as a result of trauma, but also secondary damaging factors affect the outcomes of TBI. Thus, hypoxia, hypotension, intracranial hypertension, hyperglycemia and other pathological conditions play an important role in the degree of brain damage. Extracranial complications make a certain contribution to the development of secondary brain damage and the rate of its recovery. The mechanisms of development of such complications are ambiguous, and the frequency of development, despite prevention, remains high. Complications may arise as a result of the direct impact of trauma or as a result of side effects of intensive care.